Wissenskulturen muslimischer Gesellschaften Philosophische und islamwissenschaftliche ZugängeFestschrift für Anke von Kügelgen - Moser, Kata; Tolino, Serena (Welten des Islams - Worlds of Islam - Mondes de l'Islam, 2023)
This festschrift in honor of historian of philosophy and Islamic studies scholar Anke von Kügelgen reflects her overarching research interest in the "knowledge cultures of Muslim societies." It presents contributions on individual philosophers, metaphilosophy, and religious critique in the context of the Islamic world, and on Muslim Central Asia, the transformations that have taken place in Middle Eastern societies, and historical sources.